Spesh Enterprise / Zainol Abidin Salleh... [et al.] - Salleh, Zainol Abidin; Mohd Noor, Muhammad Nadzrul; Jamdan, Shahrin; Abd Ghani, Mohd Azman (2001)
Spesh Enterpise is a company that provide and selling sport equipments. It was started on 1 January 2005.This company was located at Star Parade, Alor Setar. The business was selling sport equipment like shoes, T-shirt, Track bottom and others. It was a partnership business that include four members.